Peningkatan Hasil Belajar Siswa Melalui Pembelajaran Kontekstual Konsep Reproduksi Manusia Siswa MTs Negeri 1 Matangglumpangdua - Rusydi Rusydi; Anwar A.R (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
Teacher is one important component in improving teaching quality. One way to improve the teaching quality is by applying various innovative strategies. One of the innovative teaching strategies is contextual learning. Contextual teaching strategy is a teaching strategy which emphasize on students’ activity in learning, so that students can memorize the material for longer time and can get better achievement. This research aimed to figure out the improvement of students’ achievement in Human Reproduction Concept at MTs Negeri 1 Matangglumpangdua. This research used two cycles with four components: planning, acting, observing and reflecting. Test was conducted at the end of each cycle. Data was analyzed qualitatively by using descriptive statistic. The result shows that the average of cycle 1 increased from 70,00 to 76,09 at cycle 2. Students give positive responses 72,28%; 75, 82%; 73,39% and  71,16% to attention indicator, interest indicator, possitive belief indicator and satisfaction indicator (agreement scale) respectively. Finally, it is recommended that contextual learning is suitable to be used in Human Reproduction Concept. Nevertheless, contextual learning strategy shouldn’t be applied continously to different materials to avoid student’s boredom.